SOVEREIGNTY IN INDIA: ANALYZING THE INFLUENCE OF INTERNATIONAL TREATIES ON DOMESTIC LEGISLATION - PS, Renjini; Philipose, Geni (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the relationship between India's sovereignty and the impact of international treaties on its domestic legal system. Sovereignty, a key concept of the Indian Constitution, preserves the country's autonomy in making and enforcing laws. Globalization and the growing integration of international norms provide challenges to the traditional concept of sovereignty. This paper investigates the legal framework for incorporating international treaties into Indian domestic law, focusing on constitutional provisions, judicial interpretations, and legislative prerogatives. The article examines significant decisions and statutory enactments to illustrate the dynamics of the executive branch's treaty-making capabilities, as well as the need for parliamentary approval for treaties that affect individuals' rights. It also analyzes the balance between meeting international obligations and maintaining constitutional primacy. The study sheds light on the evolving relationship between sovereignty and international legal commitments by examining India's position within the broader global legal landscape, as well as providing insights into the potential need for reforms to improve transparency, accountability, and constitutional principles.